Evaluation of clinical use of intravenous iron: Utilization, efficacy, and safety in the management of cancer and chemotherapy-induced anemia in GI oncology. Issue 28 (1st October 2022) - Rostamnjad, Leila; Leblebjian, Houry; Falb, Jennifer; Dolan, Meghan; Sommer, Karen A.; McCleary, Nadine Jackson
Abstract : 359 Background: National Comprehensive Cancer Network recommends intravenous (IV) iron therapy for management of cancer and chemotherapy induced anemia without mentioning agent preference. Currently at Dana-Farber Cancer Institute (DFCI), all IV iron formulations can be utilized in management of iron deficiency anemia. This study was performed to evaluate the utilization, efficacy, and safety of IV iron formulations in management of cancer and chemotherapy induced iron deficiency anemia in patients with gastrointestinal (GI) cancer. Methods: Retrospective chart review was performed on DFCI patients with GI cancer undergoing palliative or adjuvant chemotherapy who received ferric gluconate, ferumoxytol, or iron sucrose between January 2021 and January 2022. Patients were identified using electronic medical record reports. Data was collected on cancer diagnosis, chemotherapy regimen, total IV iron dose and frequency, infusion reactions, laboratory values including hemoglobin, mean corpuscular volume (MCV), and iron status parameters (serum iron, ferritin, transferrin, iron-binding capacity, transferrin saturation) at baseline and 4-6 weeks after the last dose. The primary outcome was to assess the utilization of different IV iron formulations. Secondary outcomes were efficacy defined as mean absolute change from baseline in Hemoglobin levels and safety defined as incidence of hypersensitivity reactions. Results: 102 patients were evaluated of which 61 received ferumoxytol, 36 ferric gluconate and 5 iron sucrose. All patients had baseline hemoglobin (≤11 g/dL) and MCV collected. 89 patients had baseline iron status parameters (serum iron, ferritin, transferrin, iron-binding capacity, transferrin saturation). Most patients (N = 70) had diagnosis of colorectal cancer and received chemotherapy every 2 weeks. All patients received recommend total dose of IV iron on days of chemotherapy which was outside the recommended schedule of the IV iron formulations. A gradual increase in Hemoglobin concentrations in patients treated with IV iron was observed. Conclusions: Ferumoxytol and Ferric Gluconate were the most utilized IV iron formulation at DFCI GI oncology patients. All patients received recommended IV iron dosing but did not follow the recommended schedule. All patients had hemoglobin and MCV checked before each IV iron therapy. IV iron therapy was well tolerated and effective in treatment of iron-deficiency anemia in patients with gastrointestinal cancer undergoing chemotherapy.Hypersensitivity reactions were reported in 5 patients receiving ferric gluconate. Preparation Ferumoxytol Ferric Gluconate Iron sucrose Mean (± SD) hemoglobin increase g/dL 1.1 (0.1-3.8) 1.5 (0.3-3.8) 1.4 (0.4-3) Mean (± SD) MCV increase (fl) 3.5 (0.4-18) 8.3(2-15.7) 16.2 (2.5-17)